An analysis of closure signs in Korea during the COVID-19 pandemic - Lee, Hye Kyung (Linguistic Research, 2023)
This study analyzes a set of business closure signs in Korea during the COVID-19 pandemic, employing move analysis and speech act theories as analytic frameworks. In particular, as a replicated study of Ogierman and Bella (2021), it examines expressive speech acts or moves like greeting, referring, thanking, and apologizing, along with a unique Korean speech act: asking for understanding. Our findings highlight that Korean closure signs use a wider range of greetings compared to English counterparts. Referring expressions demonstrate intricate social sensitivity, indicating Korean cultural norms emphasizing politeness. Apologies in Korean signs are sometimes excessive, reflecting the importance placed on customers in Korean business culture. Repetition of thanking speech acts aims to reinforce gratitude, while the preference for sino-Korean words conveys formality and politeness. This research sheds light on the distinct linguistic and cultural features of Korean business closure signs during the pandemic, emphasizing the cultural norms governing language use. It also underscores the importance of adapting messaging strategies to cultural contexts, even in crisis situations, with potential implications for cross-cultural communication studies.
Keywords: closure signs; COVID-19; crisis communication; discursive moves; expressive speech acts